1999
DOI: 10.1258/0956462991914438
|View full text |Cite
|
Sign up to set email alerts
|

Mucinase and sialidase activity of the vaginal microflora: implications for the pathogenesis of preterm labour

Abstract: Evidence linking bacterial vaginosis (BV) to chorioamnionitis and spontaneous preterm birth is mounting. Successful treatment of BV could reduce the rate of late miscarriage and preterm birth. Mucinase and sialidase activity have been implicated in the pathogenesis of BV. This study extends the work of previous studies to investigate sialidase, other known mucin degrading enzymes and overall mucin degrading activity in samples of vaginal fluid from women with and without BV. Samples from 31 women were diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 22 publications
3
56
0
Order By: Relevance
“…BV-associated microorganisms have been recovered from the amniotic fluid of women in premature labor with intact membranes (11) and early reports have suggested that among infants delivered prematurely, the most frequent microorganisms isolated from the placenta were U. urealyticum (47%) and G. vaginalis (26%) (6). The high concentration of these BV-associated organisms has been related to the reduction of leukocytes to halt localized infection, an increased level of endotoxins and protease enzymes stimulating proinflammatory cytokine production which can result in intrauterine death, the release of sialidases and mucinases promoting placental inflammation and weakening of the chorioamniotic membrane, and an increase in the ascension of other lower genital tract organisms (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…BV-associated microorganisms have been recovered from the amniotic fluid of women in premature labor with intact membranes (11) and early reports have suggested that among infants delivered prematurely, the most frequent microorganisms isolated from the placenta were U. urealyticum (47%) and G. vaginalis (26%) (6). The high concentration of these BV-associated organisms has been related to the reduction of leukocytes to halt localized infection, an increased level of endotoxins and protease enzymes stimulating proinflammatory cytokine production which can result in intrauterine death, the release of sialidases and mucinases promoting placental inflammation and weakening of the chorioamniotic membrane, and an increase in the ascension of other lower genital tract organisms (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…These are based on the detection of bacterial amines (23-25) and bacterial sialidase (2), an enzyme produced by anaerobic flora such as Prevotella and Bacteroides spp. Sialidase promotes adhesion of bacteria to epithelia and also has mucinase activity, which may facilitate invasion of the upper genital tract by BV-associated flora (10,17,27). Elevated bacterial sialidase activity has been significantly associated with BV (2) and with preterm birth in women with BV (3, 13).…”
mentioning
confidence: 99%
“…Additional bacterial enzymes believed to play a role in the pathogenesis of BV include proteases, G. vaginalis hemolysins and mucinases (McGregor et al, 1994). Mucinase and sialidase, two hydrolytic enzymes, may enhance placental inflammation and weakening of the chorioamniotic membrane (Howe et al, 1999). These enzymes may promote increased ascending of lower genital tract organisms and sialidase increases the probability of PTB (Cauci, 2004).…”
Section: Pathogenesis Of Bacterial Vaginosismentioning
confidence: 99%